Data-driven nitrogen application for satinleaf: leveraging optical sensors in urban landscape management - Nogueira Souza Costa, Bárbara; Khoddamzadeh, Amir Ali (Frontiers in Plant Science, 2025)
The use of sensor technology is essential in managing fertilization, especially in urban landscape where excessive fertilization is a common issue that can lead to environmental damage and increased costs. This study focused on optimizing nitrogen fertilizer application for Satinleaf (Chrysophyllum oliviforme), a native Florida plant commonly used in South Florida landscaping. Fertilizer with an 8N-3P-9K formulation was applied in six different treatments: 15 g (control), 15 g (15 g twice; T1), 15 g (15 g once; T2), 30 g (15 g twice; T3), 30 g (15 g once; T4), and 45 g (15 g twice; T5). Evaluations of plant growth and nutrient status were conducted at several intervals: baseline (0), and 30, 60, 90, 120, 150, and 180 days post-fertilizer application. Three types of optical sensors-GreenSeeker™, SPAD meter, and atLEAF chlorophyll sensor - were used to monitor chlorophyll levels as an indicator of nitrogen content. The study found that the 30 g (15 g twice; T3) treatment was most effective in promoting plant growth and increasing nitrogen content in leaves and soil, while the 45 g (15 g twice; T5) treatment resulted in higher nutrient runoff, indicating potential environmental risks. These findings emphasize the value of using optical sensors for precise nitrogen management in plant nurseries to enhance growth, lower costs, and minimize environmental impact.